Biomass-based water-dispersible polyurethane resin complexed with cellulose nanofibers, Manufacturing method thereof, and Eco-friendly, highly durable polyurethane film comprising the same
Patent Information
- Application Number
- KR1020250199062
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-15
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-12-15
Abstract
Description
Technology Field
[0001] The present invention relates to a water-dispersible polyurethane resin containing a high content of biomass with improved durability by introducing cellulose nanofibers, and a film using the same. Background Technology
[0002] Polyurethane is widely used in various industrial fields, such as coatings, adhesives, synthetic leather, and films, due to its excellent elasticity, wear resistance, and ease of processing. In line with recent stricter environmental regulations and the trend toward carbon neutrality, the transition from conventional solvent-based polyurethanes, which use organic solvents, to water-dispersible polyurethanes (WPUs), which use water as a solvent, is accelerating. Furthermore, research on biomass-based polyurethanes derived from plant-based materials is active to reduce dependence on petroleum-based raw materials. However, despite the advantage of being eco-friendly, biomass-based water-dispersible polyurethanes have been limited in their application in industries requiring high performance due to the disadvantage of having somewhat lower mechanical properties, such as tensile strength and heat resistance, compared to conventional petroleum-based solvent-based polyurethanes. Although research involving the addition of inorganic nanoparticles has been conducted to overcome this, problems such as increased specific gravity or reduced dispersion stability may occur. Accordingly, there are attempts to utilize cellulose nanofibers, which are lightweight, high-strength, and eco-friendly materials, as reinforcing agents; however, there is an urgent need for technology that can effectively enhance physical properties through the uniform dispersion of hydrophilic cellulose nanofibers and the formation of structural networks within a hydrophobic polyurethane matrix. Prior art literature
[0003] Republic of Korea Published Patent No. 10-2023-0171870 (Published Dec. 21, 2023) The problem to be solved
[0004] The objective of the present invention is to provide a sustainable, eco-friendly material that reduces carbon emissions and minimizes the impact on human health and the environment by developing a water-dispersible polyurethane using plant-based biomass raw materials such as corn and castor beans, in order to overcome the environmental problems and functional limitations of existing petroleum-based polyurethanes and general bio-polyurethanes, thereby excluding the use of harmful organic solvents.
[0005] In addition, the present invention aims to provide a highly durable polyurethane film with improved mechanical properties, such as tensile strength and heat resistance, by introducing cellulose nanofibers through an optimal process to induce a physical crosslinking effect within the resin. means of solving the problem
[0006] The present invention, for achieving the above-mentioned purpose, provides a method for manufacturing a water-dispersible polyurethane resin composited with cellulose nanofibers, comprising the following steps: Step 1: mixing and stirring a biomass-derived polyol, an emulsifier, and cellulose nanofibers to produce a mixture in which cellulose nanofibers are dispersed; Step 2: cooling the mixture to 50 to 100°C, then adding a diisocyanate to perform a polymerization reaction to produce a urethane prepolymer composited with cellulose nanofibers, and then adding a neutralizing agent to neutralize it; Step 3: adding water to the neutralized cellulose nanofiber composite urethane prepolymer to form a water-dispersible urethane dispersion; and Step 4: adding a chain extender to the dispersion and reacting it to obtain a water-dispersible polyurethane resin composited with cellulose nanofibers.
[0007] In addition, the present invention provides a biomass-based water-dispersible polyurethane resin composited with cellulose nanofibers prepared by the method described above.
[0008] In addition, the high-durability polyurethane film of the present invention is a molded article of a film-forming resin comprising a biomass-based water-dispersible polyurethane resin composited with cellulose nanofibers manufactured by the above manufacturing method, and can satisfy a biocarbon content of 50 to 70 weight% as measured according to ASTM D 6866-12 Method-B, a tensile strength of 30 N / mm² or more, and a softening point of 160°C or more. Effects of the invention
[0009] According to the present invention, by using biomass-based raw materials for both the main raw material, polyol, and the chain extender, and by using naturally derived materials for the reinforcing material, cellulose nanofiber, the bio-carbon content of the final product is increased, resulting in an excellent carbon reduction effect. In particular, cellulose nanofibers uniformly dispersed within the resin form hydrogen bonds and physical entanglements with polyurethane chains, providing significantly improved durability compared to conventional bio-water-dispersible polyurethane. The present invention realizes a sustainable high-performance material through the utilization of renewable resources and the exclusion of harmful substances, which can be evaluated as an innovative technology that meets the demands of modern industry for environmental protection and high-quality products.
[0010] In addition, harmful effects on the human body and the environment can be minimized through a water dispersion process that does not use organic solvents. Specific details for implementing the invention
[0011] The present invention will be described in detail below.
[0012] The present invention relates to a highly durable polyurethane film with maximized mechanical strength and durability, wherein cellulose nanofibers are uniformly composited within the matrix of the polyurethane film by applying an in-situ polymerization process in which cellulose nanofibers are introduced from the initial synthesis stage during the production of an eco-friendly water-dispersible polyurethane resin based on biomass-derived raw materials.
[0013] The water-dispersible polyurethane resin composited with cellulose nanofibers according to the present invention is manufactured by performing the following process.
[0014] A process comprising: Step 1, mixing and stirring a biomass-derived polyol, an emulsifier, and cellulose nanofibers to prepare a mixture in which cellulose nanofibers are dispersed; Step 2, cooling the first mixture, adding a diisocyanate to perform a polymerization reaction to prepare a urethane prepolymer composited with cellulose nanofibers, and then adding a neutralizing agent to neutralize it; Step 3, adding water to the neutralized prepolymer to form a water-dispersible urethane dispersion; and Step 4, adding a chain extender to the dispersion and reacting it to obtain a water-dispersible polyurethane resin composited with cellulose.
[0015] The biomass-derived polyol in step 1 is a key raw material that forms soft segments of resin chains to impart flexibility to the final film, and can take various forms such as polyester, polyether, and polycarbonate polyols; it is preferable that the biomass content be 80 to 100 weight percent. Such a high bio content maximizes the contribution to carbon neutrality of the final product.
[0016] In addition, the biomass-derived polyol in step 1 is a polyol with a weight-average molecular weight of 500 to 2,000, preferably 1,000 to 1,300, and is an ether-type polyol derived from plant biomass such as corn and castor beans. At this time, if the weight-average molecular weight of the biomass-derived polyol is less than 500, the chain becomes short, resulting in insufficient length of the soft segment. Consequently, the proper balance with the hard segment within the water-dispersible polyurethane resin polymer network is disrupted, which may lead to an excessively high crosslinking density. As a result, the final product may become excessively rigid and brittle, leading to problems such as reduced flexibility and tensile strength. If the weight-average molecular weight of the biomass-derived polyol is 2,000 or more, the soft segment becomes excessively long, increasing the distance between crosslinking points. Consequently, the crosslinking density of the polymer network decreases, resulting in insufficient mechanical strength and wear resistance. Furthermore, a high molecular weight can significantly increase the viscosity of the reaction mixture, thereby impeding processability and dispersion stability.
[0017] In addition, it is preferable to use one or more of the emulsifier selected from dimethylolbutanoic acid (DMBA) and dimethylolpropionic acid (DMPA) as the emulsifier in the first step. The amount added is 10 to 15 parts by weight per 100 parts by weight of the polyol. This range is the optimal formulation range that ensures sufficient hydrophilic ionic groups so that resin particles can be stably dispersed without aggregation in the subsequent water dispersion process, while simultaneously preventing a decrease in the water resistance of the final film due to excessive hydrophilic groups. If the amount of the emulsifier used is less than 10 parts by weight, the density of hydrophilic groups is insufficient, resulting in reduced water dispersion stability; if it is used in excess of 15 parts by weight, the polyurethane resin becomes excessively hydrophilic, causing a problem where the water resistance of the polyurethane film manufactured using it is severely reduced; therefore, the above range is the range for optimal physical properties.
[0018] In addition, the cellulose nanofibers of step 1 are mixed with a polyol. At this time, it is preferable to use surface-modified cellulose nanofibers to improve compatibility with hydrophobic polyols and emulsifiers and to ensure dispersibility. Specifically, the surface-modified cellulose nanofibers may include one or more selected from acetylated cellulose nanofibers, hydrophobically modified TEMPO-oxidized cellulose nanofibers, carboxymethylated cellulose nanofibers, and esterified cellulose nanofibers.
[0019] In addition, it is advantageous to use an amount of cellulose nanofibers in the range of 0.5 to 6.0 parts by weight relative to 100 parts by weight of resin solids, preferably 1.0 to 5.0 parts by weight, and more preferably within the range of 2.5 to 5.0 parts by weight, in terms of securing excellent physical properties. At this time, if the cellulose nanofiber content is less than 0.5 parts by weight, the amount used is too small, so there is no or negligible effect of improving durability due to its use; if it is used in excess of 6.0 parts by weight, the aggregation between nanofibers is intensified due to excessive use, which reduces dispersion stability and may lead to a problem where the physical properties of the final composite resin actually deteriorate; therefore, it is appropriate to use it within the above range. Furthermore, there is a tendency for it to be more advantageous as the aspect ratio (AR: Fiber Aspect Ratio) of the cellulose nanofibers increases, and cellulose nanofibers with a high aspect ratio physically intertwine with polymer chains from the resin synthesis stage to form a strong three-dimensional network structure. This effectively disperses and transmits stress throughout the network when it is applied to the final film, thereby improving mechanical properties such as tensile strength. Also, the optimal aspect ratio of the cellulose nanofiber is appropriately about 30 to 300.
[0020] In addition, the mixing and stirring of the first step is carried out under a nitrogen atmosphere, the mixing and stirring temperature is in the range of 80 to 150°C, preferably 90 to 110°C, and the stirring speed is set to 100 to 300 rpm and carried out for 30 to 50 minutes.
[0022] The next step, step 2, is the prepolymer synthesis and neutralization process. After cooling the mixture from step 1 to 50 to 100°C, preferably 50 to 70°C, a diisocyanate is added, and a polymerization reaction is performed to synthesize a prepolymer.
[0023] The above diisocyanates are isophorone diisocyanate (IPDI) and 4,4'-methylene dicyclohexyl diisocyanate (H 12Aliphatic or alicyclic compounds with excellent yellowing resistance, such as MDI and / or hexamethylene diisocyanate (HDI), may be used. Furthermore, the amount added is 60 to 90 parts by weight, preferably 65 to 88 parts by weight, and more preferably 70 to 85 parts by weight, relative to 100 parts by weight of the biomass-derived polyol in the first step. This amount is a key variable that controls the density of the hard segment and the NCO / OH equivalent ratio to determine the mechanical strength and thermal stability of the final resin. If the amount of diisocyanate added is less than 60 parts by weight, the reaction with the biomass-derived polyol proceeds incompletely, and sufficient urethane bonds may not be formed. Consequently, the molecular weight of the polymer chains decreases, and the degree of crosslinking becomes insufficient, which may lead to reduced durability, mechanical strength, and chemical stability. As a result, in applications requiring durability and elasticity, such as films or clothing, there is a risk of product performance degradation or appearance defects. In addition, if the amount of diisocyanate added exceeds 90 parts by weight, in addition to the reaction with the biomass-derived polyol, the excessive isocyanate may cause internal reactions or adverse reactions with moisture, leading to excessive crosslinking. Excessive crosslinking makes the polymer network too dense, causing the product to become overly hardened, brittle, and lose flexibility. Furthermore, if carbon dioxide is generated due to adverse reactions with moisture, problems such as bubble formation or reduced film uniformity may occur.
[0024] Then, when the polymerization reaction is completed, a neutralizing agent is added to the reaction solution containing the urethane prepolymer composited with cellulose nanofibers to neutralize it, thereby producing a neutralized urethane prepolymer composited with cellulose nanofibers.
[0025] The above neutralizing agent may include one or more selected from triethylamine (TEA), triethanolamine (TEOA), and diisopropanolamine (DIPA), and preferably may include TEA. At this time, the amount of neutralizing agent added is 5 to 15 parts by weight, preferably 6.0 to 14.0 parts by weight, and more preferably 6.5 to 12.5 parts by weight, relative to 100 parts by weight of the polyol in the first step, to ionize the carboxyl groups of the emulsifier and maximize dispersion stability. At this time, if the amount of neutralizing agent added is less than 5 parts by weight, sufficient neutralization of the carboxyl groups does not occur, which may result in lower hydrophilicity of the resin particles. Consequently, the dispersion stability of the emulsion decreases, and phenomena such as particle aggregation or precipitation may occur. As a result, the appearance of the final film or coating becomes non-uniform, and water resistance and durability are reduced, which may have a negative impact on the quality of the product. In addition, if the amount of neutralizing agent added exceeds 15 parts by weight, excessive neutralization may impart unnecessary hydrophilicity to the resin, which may lead to a decrease in the film's water resistance and increased water absorption, thereby posing a risk of reduced mechanical strength or wear resistance. Furthermore, an excessive amount of neutralizing agent can destabilize the pH of the final product, causing additional chemical instability, which may adversely affect the overall properties of the resin.
[0026] And, after adding the neutralizing agent, the neutralization reaction can be carried out for 10 to 50 minutes, preferably 25 to 40 minutes, while stirring slowly.
[0028] Next, Step 3 is a phase-shifting dispersion process in which water is added dropwise and stirred to the urethane prepolymer composited with neutralized cellulose nanofibers prepared in Step 2 to form a water-dispersible urethane dispersion. At this time, the dropwise addition is performed while stirring at a stirring speed of 800 to 1,800 rpm, preferably 1,000 to 1,500 rpm; if the speed is too low, phase separation may occur, causing the resin to harden or water to remain at the bottom of the reactor.
[0029] The water-dispersible polyurethane of the present invention uses a large amount of water as a solvent, and the amount of water added is 800 to 950 parts by weight, preferably 850 to 950 parts by weight, relative to 100 parts by weight of the polyol in the first step. By adding such a sufficient amount of water and stirring at high speed, the increase in viscosity is controlled, and a stable emulsion composed of fine resin particles is formed. If the amount of water falls outside this range, aggregation of resin particles may occur, or conversely, the drying time may become excessively long, which may reduce process efficiency.
[0031] Next, step 4 is a chain extension process in which a water-dispersible polyurethane resin is synthesized by cooling the water-dispersible urethane dispersion and then adding and reacting a chain extender.
[0032] The above chain extender may include one or more selected from biomass-based 1,3-propanediol, petroleum-based 1,3-propanediol, petroleum-based 1,4-butylene glycol, or petroleum-based 1,6-hexamethylene glycol, and preferably may include biomass-based 1,3-propanediol.
[0033] In particular, among the chain extenders mentioned above, the biomass-based 1,3-propanediol is manufactured through the fermentation process of corn, a renewable resource, thereby enhancing environmental sustainability while offering the advantage of a reduced carbon footprint compared to petroleum-based raw materials during the production process. In terms of chemical structure, biomass-based 1,3-propanediol is structurally identical to petroleum-based 1,3-propanediol and possesses a relatively short carbon chain (three carbons) and two hydroxyl groups, contributing to the formation of soft segments in water-dispersible urethane resins. Consequently, microphase separation and mechanical properties such as flexibility and elasticity can be controlled in the final polymer network. On the other hand, petroleum-based diols such as 1,4-butylene glycol and 1,6-hexamethylene glycol have longer chains or are designed with different structures, which results in the disadvantage of reduced reactivity of water-dispersible polyurethane (WPU) under the same conditions.
[0034] A high molecular weight water-dispersible polyurethane resin is completed by adding the chain extender to the aqueous dispersion and reacting it with the residual NCO ends of the prepolymer. It is appropriate to use 8 to 15 parts by weight of the chain extender per 100 parts by weight of the polyol in the first step. This effectively increases the molecular weight of the polymer chain, thereby securing the mechanical properties of the final film and improving wear resistance. At this time, if the amount of chain extender used is less than 8, the extension of the polymer chain proceeds insufficiently, resulting in a lower molecular weight and a lower crosslinking density within the polymer network. Consequently, the mechanical performance of the final product, such as tensile strength, elongation, and wear resistance, may be degraded, and problems such as difficulty in achieving a uniform coating during film formation may occur. If the amount exceeds 15 parts by weight, excessive extension and crosslinking occur, causing the polymer network to be formed too densely. As a result, the resin becomes too hard, leading to reduced flexibility, increased brittleness, and worsening processability due to an increase in the viscosity of the reaction mixture.
[0035] In particular, the use of a biomass-based chain extender contributes to maintaining the biocarbon content of the final water-dispersible polyurethane resin at 50% by weight or more, preferably 50 to 70% by weight, and more preferably 60.0 to 70.0% by weight, which is an important factor in realizing the ultimate goal of the present invention, which is environmentally friendly carbon footprint reduction.
[0037] After preparing a film-forming resin using the above-described water-dispersible polyurethane resin alone or additionally using other additives, an eco-friendly, high-durability polyurethane film, which is a molded body, can be manufactured using the same.
[0038] The film-forming resin above is suitable for having an optimal viscosity of 6,500 to 8,000 cps at a temperature of 25℃, preferably 6,700 to 7,500 cps.
[0039] In addition, the above film-forming resin may further use a general viscosity modifier used for viscosity control.
[0040] In addition, the film-forming resin may further include a surfactant, a crosslinking agent, a catalyst, a stabilizer, a dispersant, a filler, etc., as needed.
[0041] A high-durability polyurethane film can be manufactured by performing the following steps: coating a film-forming resin onto a substrate, performing a first heat treatment for 60 to 90 seconds at a temperature of 65 to 80°C, performing a second heat treatment for 60 to 90 seconds at a temperature of 100 to 140°C, and aging the cured product after the second heat treatment.
[0043] The high-durability water-dispersible polyurethane film of the present invention described above may have a biocarbon content of 50 weight% or more, preferably 55 to 70 weight%, and more preferably 60 to 70 weight% when measured according to ASTM D 6866-12 Method-B.
[0044] In addition, the polyurethane film of the present invention has a tensile strength of 30 N / mm² as measured according to ASTM D 882. 2 The above, preferably 35 N / mm 2 The above is, more preferably 40.0 to 50.0 N / mm 2 It is possible to provide a highly durable film that satisfies [specific criteria].
[0045] In addition, the polyurethane film of the present invention can satisfy an elongation of 400 to 600%, preferably 420 to 560%, and more preferably 430 to 520% as measured according to ASTM D 882.
[0046] In addition, the polyurethane film of the present invention has a 100% modulus of 6.0 N / mm² as measured according to ASTM D 882. 2 The above, preferably 6.0 to 13.0 N / mm 2 8.0 to 12.5 N / mm 2 It can satisfy.
[0047] In addition, when measured using a dynamic mechanical analyzer (DMA), the polyurethane film of the present invention may have a softening point of 160°C or higher, preferably 162°C to 187°C, and more preferably 168°C to 185°C.
[0049] This invention contributes significantly to realizing eco-friendly sustainability by actively utilizing renewable biomass-derived raw materials and adopting a water-dispersion process that excludes organic solvents. In particular, the technology for forming a three-dimensional network structure through the introduction of cellulose nanofibers has fundamentally overcome the limitations of mechanical property degradation observed in existing bio-based resins. As an innovative technology that satisfies both the environmental protection and the modern industrial demands for high-performance products, it can be widely applied to various high-functional fields requiring both high durability and eco-friendliness, such as clothing coatings, industrial protective films, building interior materials, and automotive materials.
[0051] The present invention will be explained in more detail below through examples, but the following examples are not intended to limit the scope of the invention and should be interpreted as being for the purpose of aiding understanding of the invention.
[0052] [Example]
[0053] Example 1: Preparation of water-dispersible polyurethane resin and film
[0054] (1) Preparation of biomass-based water-dispersible polyurethane resin with cellulose nanofiber composite
[0055] Biomass-derived polyol, an emulsifier, and surface-modified cellulose nanofibers were introduced into a four-necked reactor equipped with a stirrer in the compositional ratios listed in Table 1. This was mixed and stirred for 30 minutes at a speed of 200 rpm under a nitrogen stream at 90°C to prepare a mixture in which the cellulose nanofibers were uniformly dispersed within the polyol (Step 1).
[0056] Here, a corn-derived biopolyol with a weight-average molecular weight of approximately 2,000 (manufacturer: SK Chemicals, trade name: ECOTRION H2000, biomass content: 100%) was used as the biomass-derived polyol, DMBA (Dimethylolbutanoic Acid) was used as the emulsifier, and hydrophobically modified cellulose nanofibers (manufacturer: ANPOLY, trade name: Polycellu) were used for stable dispersion. TM T-CNF (aspect ratio of 50 to 200) was used.
[0057] Next, the mixture was cooled to 70°C, hexamethylene diisocyanate (HDI) was added as a diisocyanate in the composition ratio listed in Table 1, and the temperature was raised to 95°C to perform a polymerization reaction for 2.5 hours to prepare a prepolymer composited with cellulose nanofibers. Subsequently, the mixture was cooled to 90°C and triethylamine (TEA), a neutralizing agent, was added and neutralized for 30 minutes to prepare a neutralized prepolymer (Step 2).
[0058] Next, distilled water was added to the previously prepared neutralized prepolymer under high-speed stirring of 1,000 rpm to induce a phase transition, thereby forming a water-dispersible urethane dispersion (Step 3).
[0059] Next, the water-dispersible urethane dispersion was cooled to 35°C, then biomass-based 1,3-propanediol (Bio-PDO) was added as a chain extender and reacted for 1 hour to finally obtain a water-dispersible polyurethane resin in which cellulose nanofibers were composited into a three-dimensional network (Step 4).
[0060] (2) Manufacturing of high-durability polyurethane film
[0061] A water-dispersible polyurethane resin prepared earlier was bar-coated onto a release liner, then subjected to a first heat treatment at 70°C for 2 minutes to dry out moisture, and subjected to a second heat treatment at 130°C for 2 minutes to cure, and then aged at room temperature for 24 hours to produce a high-durability polyurethane film with a thickness of approximately 38 μm.
[0063] Examples 2 to 3
[0064] Examples 2 and 3 were prepared in the same manner as Example 1, but with the content of cellulose nanofibers added in the first step changed as shown in Table 1 below.
[0066] Comparative Example 1
[0067] A water-dispersible polyurethane resin and film were prepared by the same method as in Example 1, but without adding cellulose nanofibers in the first step, and by mixing only a biomass-derived polyol and an emulsifier.
[0069] Comparative Example 2
[0070] It was prepared in the same manner as in Example 1, except that polytetramethylene ether glycol (PTMG, Mw 2,000), a petroleum-based polyol, was used instead of a biomass-derived polyol, petroleum-based 1,4-butanediol was used as a chain extender, and cellulose nanofibers were not added.
[0072] Comparative Example 3
[0073] A water-dispersible polyurethane resin and film were prepared using the same method as in Example 1, but with 7 parts by weight of cellulose nanofiber used in the first step.
[0075] Comparative Example 4
[0076] A water-dispersible polyurethane resin without cellulose nanofibers was first prepared in the same manner as Comparative Example 1, and then, immediately before the film formation step, a water-dispersible solution of cellulose nanofibers was simply added and stirred in the same amount as in Example 1 to prepare a film.
[0077] Classification (weight part) Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Biomass-based polyols (corn-based) 100 100 100 100 - 100 100 Petroleum-based polyol (PTMEG) - - - - 100 - - emulsifier 14.0 14.0 14.0 14.0 14.0 14.0 14.0 Cellulose nanofibers 1.5 3.5 5.0 - - 7.0 1.5 Diisocyanate (HDI) 82.0 82.0 82.0 82.0 82.0 82.0 82.0 corrector 9.8 9.8 9.8 9.8 9.8 9.8 9.8 water 900 900 900 900 900 900 900 Chain extender (1,3-propanediol) Bio-industry 12.5 12.5 12.5 12.5 - 12.5 12.5 petroleum-based - - - - 11.0 - - Synthesis method in-situ in-situ in-situ - - in-situ ex-situ
[0079] Experimental Example 1: Measurement of Mechanical Properties and Biocarbon Content
[0080] For each of the polyurethane films prepared in Examples 1 to 3 and Comparative Examples 1 to 4 above, the tensile strength (N / mm²) according to ASTM D 882 2 ), elongation (%) and 100% modulus (N / mm 2 ) was measured.
[0081] In addition, the biocarbon content (weight%) was measured according to ASTM D 6866-12 Method-B, and the results are shown in Table 2 below.
[0082] division Tensile strength (N / mm²) 2 ) Growth Rate (%) 100% Modulus (N / mm) 2 ) Biocarbon content (weight%) Example 1 36.2 560 6.5 60.5 Example 2 43.8 510 9.2 61.2 Example 3 47.5 450 12.1 61.8 Comparative Example 1 21.0 630 3.2 60.1 Comparative Example 2 23.5 600 3.5 5.0 or lower Comparative Example 3 22.7 600 3.4 62.6 Comparative Example 4 26.8 500 4.5 60.4
[0083] As shown in the measurement results of Table 2 above, the films of Examples 1 to 3, prepared using a biomass-based water-dispersible polyurethane resin composited with cellulose nanofibers in a situ manner, exhibited a tensile strength improvement of approximately 1.7 to 2.2 times or more compared to the film of Comparative Example 1, prepared with a water-dispersible polyurethane resin without added cellulose nanofibers, with all measuring 30 N / mm². 2 The results exceeded the above, and the modulus was very high compared to Comparative Example 1, while the elongation was lower.
[0084] In addition, the film of Comparative Example 3, prepared using a polyurethane resin prepared using more than 6 parts by weight and 7 parts by weight of cellulose nanofibers, showed a result in which mechanical properties actually decreased compared to Example 3.
[0085] On the other hand, the film of Comparative Example 4, prepared using a biomass-based water-dispersible polyurethane resin composited with cellulose nanofibers in an ex-situ manner, showed a result that did not show a significant improvement in tensile strength and modulus compared to Example 1, even though the same amount of cellulose nanofibers was used.
[0087] Experimental Example 2: Heat Resistance Evaluation
[0088] The heat resistance of the films prepared in Examples 1 to 3 and Comparative Example 1 was evaluated as follows.
[0089] For the heat resistance evaluation, the change in storage modulus with increasing temperature was measured using Dynamic Mechanical Analysis Ratio (DMA), and the temperature at which the modulus begins to decrease rapidly was defined as the softening point for comparison.
[0090] To verify the results according to the amount of cellulose nanofiber added, an experiment was conducted using Comparative Example 1 as a control group. The results are shown in Table 3 below.
[0091] division Softening point (°C) note Example 1 162 Improved heat resistance Example 2 175 Excellent heat resistance Example 3 183 Excellent heat resistance Comparative Example 1 140 Standard (no cellulose nanofiber added)
[0092] As can be seen from the results in Table 3 above, it was confirmed that the films of Examples 1 to 3, prepared using a resin in which cellulose nanofibers were composited in a sit-in manner, had a softening point that increased by more than 20°C compared to Comparative Example 1, which was the group without additives. Through this, it was confirmed that the film using cellulose nanofibers but with a resin composited in a sit-in manner has an excellent effect in improving heat resistance.
[0093] In conclusion, while general bio-based polyurethanes tend to have somewhat lower thermal stability compared to petroleum-based ones, it was confirmed that the polyurethane film prepared using the biomass-based water-dispersible polyurethane resin composited with cellulose nanofibers of the present invention showed improved mechanical properties, and that the dispersed cellulose nanofibers had the effect of improving heat resistance.
[0095] Through the above examples and experimental examples, it was confirmed that a highly durable polyurethane film can be provided by improving heat resistance along with excellent mechanical properties thanks to the physical crosslinking effect of the cellulose nanofiber network. This invention satisfies both environmental protection and high performance requirements and can be widely utilized in various high-functional applications such as clothing coatings, industrial protective films, and automotive interior materials.
Claims
Claim 1 Step 1: mixing a biomass-derived polyol having a biomass content of 80 to 100 weight%, an emulsifier, and cellulose nanofibers, and stirring at 80 to 150°C to prepare a mixture in which cellulose nanofibers are dispersed; Step 2: cooling the mixture to 50 to 100°C, adding a diisocyanate to perform a polymerization reaction to prepare a urethane prepolymer composited with cellulose nanofibers, and then adding a neutralizing agent to neutralize it; Step 3: adding water to the neutralized cellulose nanofiber composite urethane prepolymer to form a water-dispersible urethane dispersion; A process comprising: step 4, adding and reacting a chain extender to the dispersion to obtain a water-dispersible polyurethane resin composited with cellulose nanofibers; wherein the biomass-derived polyol comprises one or more selected from polyester polyol, polyether polyol, and polycarbonate polyol, the cellulose nanofiber of step 1 is a hydrophobically modified cellulose nanofiber, and the cellulose nanofiber of step 1 comprises 1.0 to 5 parts per 100 parts by weight of the biomass-derived polyol of step 1.The method is characterized by using 0 parts by weight, wherein the cellulose nanofiber has a fiber aspect ratio (AR) of 30 to 300, wherein the diisocyanate of the second step is hexamethylene diisocyanate (HDI), wherein the diisocyanate is added in an amount of 60 to 90 parts by weight per 100 parts by weight of the biomass-derived polyol of the first step, wherein the water of the third step is added in an amount of 800 to 950 parts by weight per 100 parts by weight of the biomass-derived polyol of the first step, wherein the chain extender of the fourth step is added in an amount of 8 to 15 parts by weight per 100 parts by weight of the biomass-derived polyol of the first step, and wherein the chain extender comprises one or more selected from biomass-based 1,3-propanediol, petroleum-based 1,3-propanediol, petroleum-based 1,4-butylene glycol, or petroleum-based 1,6-hexamethylene glycol. A method for manufacturing a biomass-based water-dispersible polyurethane resin composited with cellulose nanofibers. Claim 2 delete Claim 3 delete Claim 4 A method for manufacturing a biomass-based water-dispersible polyurethane resin composited with cellulose nanofibers, wherein, in claim 1, the emulsifier comprises one or more selected from DMBA (Dimethylol butanoic acid) and DMPA (Dimethylolpropionic acid), and is used in an amount of 10 to 15 parts by weight per 100 parts by weight of the biomass-derived polyol in step 1. Claim 5 delete Claim 6 delete Claim 7 A method for manufacturing a biomass-based water-dispersible polyurethane resin composited with cellulose nanofibers, characterized in that, in claim 1, the neutralizing agent of the second step comprises one or more selected from triethylamine (TEA), triethanolamine (TEOA), and diisopropanolamine (DIPA), and is added in an amount of 5 to 15 parts by weight per 100 parts by weight of the biomass-derived polyol of the first step. Claim 8 delete Claim 9 delete Claim 10 A water-dispersible polyurethane resin composited with cellulose nanofibers, characterized by being manufactured by the method of claim 1, 4, or 7. Claim 11 A molded article of a film-forming resin comprising the water-dispersible polyurethane resin of claim 10, wherein the biocarbon content measured according to ASTM D 6866-12 Method-B is 60 to 70 wt% and the tensile strength measured according to ASTM D 882 is 35.0 to 50.0 N / mm 2 The elongation is 420–560%, and the 100% modulus is 6.0–13.0 N / mm 2 Eco-friendly, high-durability polyurethane film characterized by satisfying [specific criteria]. Claim 12 In claim 11, the above-mentioned polyurethane film is an eco-friendly, high-durability polyurethane film characterized by having a softening point of 160°C or higher as measured using a dynamic mechanical analyzer (DMA).
Citation Information
Patent Citations
Preparation method of plant fiber in-situ reinforced polyurethane composite material
CN114230822A
Polyol dispersion for production of polyurethane foam containing colorant and cellulose nanofiber
JP2021070781A
Manufacturing method of highly stretchable water-dispersible polyurethane resin containing biomass-derived polyol and polyurethane film thereof
KR102738973B1